2020
DOI: 10.3390/polym12010104
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Protein Immobilization on Polymers—A Plasma Surface Activation Study

Abstract: Over the last years, polymers have gained great attention as substrate material, because of the possibility to produce low-cost sensors in a high-throughput manner or for rapid prototyping and the wide variety of polymeric materials available with different features (like transparency, flexibility, stretchability, etc.). For almost all biosensing applications, the interaction between biomolecules (for example, antibodies, proteins or enzymes) and the employed substrate surface is highly important. In order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…This evidence demonstrates that air-plasma treatment can significantly improve the biocompatibility of inorganic implants and may be conducive for osteogenesis. After air-plasma treatment, hydroxyl radicals are added to the treated surface (Tsougeni et al, 2015;Kurzyp et al, 2017;Sathish et al, 2019;Wieland et al, 2020;Zhang et al, 2020), further reducing water contact angle shown in Figure 4, which forms an adsorption effect with adhesion proteins and enhances biocompatibility. Hydrophilicity is critical for the bioactivity of bone tissue implants and can improve cell adhesion and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…This evidence demonstrates that air-plasma treatment can significantly improve the biocompatibility of inorganic implants and may be conducive for osteogenesis. After air-plasma treatment, hydroxyl radicals are added to the treated surface (Tsougeni et al, 2015;Kurzyp et al, 2017;Sathish et al, 2019;Wieland et al, 2020;Zhang et al, 2020), further reducing water contact angle shown in Figure 4, which forms an adsorption effect with adhesion proteins and enhances biocompatibility. Hydrophilicity is critical for the bioactivity of bone tissue implants and can improve cell adhesion and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…HP is an immune-mediated interstitial lung disease occurring in susceptible individuals [1][2][3]. Importantly, in a number of cases, HP can lead to pulmonary fibrosis, which is associated Biosensors 2021, 11,196 2 of 16 with progressive respiratory insufficiency and death. Exposure may occur indoors, at work, at home, or even outdoors in recreational environments.…”
Section: Introductionmentioning
confidence: 99%
“…Recent combined progress in microtechnology and precise protein immobilization on a variety of materials allowed for the development of microfluidic platforms designed as low cost easily operated point-of-care (PoC) biosensing systems offering a broader availability in locations where the use of costly and complex instruments is not an option [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The mouse IgG antibodies labelled with two different methods were used. Reproduced from Wieland et al (2020) [ 40 ] under conditions of the CC BY license.…”
Section: Figurementioning
confidence: 99%